Advancements in Skin Delivery of Natural Bioactive Products for Wound Management: A Brief Review of Two Decades - Cameron Ryall; Sanjukta Duarah; Shuo Chen; Haijun Yu; Jingyuan Wen (MDPI AG, 2022)
Application of modern delivery techniques to natural bioactive products improves their permeability, bioavailability, and therapeutic efficacy. Many natural products have desirable biological properties applicable to wound healing but are limited by their inability to cross the stratum corneum to access the wound. Over the past two decades, modern systems such as microneedles, lipid-based vesicles, hydrogels, composite dressings, and responsive formulations have been applied to natural products such as curcumin or aloe vera to improve their delivery and efficacy. This article reviews which natural products and techniques have been formulated together in the past two decades and the success of these applications for wound healing. Many cultures prefer natural-product-based traditional therapies which are often cheaper and more available than their synthetic counterparts. Improving natural products' effect can provide novel wound-healing therapies for those who trust traditional compounds over synthetic drugs to reduce medical inequalities.